Studies on Colombo-Curing of Mackerel - Balachandran, K. K.; Muraleedharan, V. (Fishery Technology, 1975)
Results of investigations carried out to improve the process of 'Colombo-curing' of mackerel are presented in this paper. Optimum composition of salt and goruka puli (malabar tamarind, Garcinia cambogea) to be used in the pickle mixture to give a product of good organoleptic and chemical characteristics have been worked out. Sodium benzoate is used as a preservative against the attack of molds, 'red' etc.